An acoustic/thermo-responsive hybrid system for advanced doxorubicin delivery in tumor treatment. (26th February 2020) - Zhang, Li; Zhang, Shiyu; Chen, Huajian; Liang, Yu; Zhao, Bingxia; Luo, Wanxian; Xiao, Qian; Li, Jinheng; Zhu, Junqiao; Peng, Chao; Zhang, Yaru; Hong, Zhe; et al.
Abstract : Ultrasound-assisted fast extravasation and the following laser-triggered drug release of thermo-sensitive liposomes synergistically enhanced drug delivery in deep tumors. Abstract : The efficiency of drug delivery and bioavailability to tumor cells are crucial for effective cancer chemotherapy. Herein, a doxorubicin (DOX) encapsulated lysolipid-based thermosensitive liposome decorated with cRGD peptide (RTSL) is conjugated on the surface of an IR780-loaded microbubble (IMB) to synthesize RTSL-IMBs. Sequentially taking advantage of acoustic-assisted early extravasation and thermo-triggered interstitium ultrafast drug release, RTSL-IMBs combine with ultrasound (US) and laser irradiation can advance drug delivery and bioavailability. In vitro experiments demonstrate that RTSL-IMBs associated with a two-step protocol (subsequently US irradiation for 1 min and laser irradiation for 5 min) can dramatically enhance the cellular uptake and bioavailability of DOX. In vivo fluorescence imaging studies reveal that the combination of RTSL-IMBs and US shows a 2.8-fold intratumoral drug accumulation increase at 0.5 h post-injection, while it will take 48 h to reach the same level of intratumoral drug accumulation for the RTSL-IMB group alone. Interestingly, the following localized application of a laser can further increase drug accumulation and slow tumor clearance. Histological analysis demonstrates that the combinational RTSL-IMBs, US and laser significantly improve the drug penetration distance and delivery efficiency in the tumor core. In this study, the acoustic/thermo-responsive hybrid system shows potential for advancing DOX chemotherapy in breast cancer cell MCF-7 xenograft nude mice.